Analysis of Determinants of Covid-19 Incidence in Indonesian National Army Training Soldiers in 2020 - Muniroh, Muniroh; Cahyati, Widya Hary; Ratna Rahayu, RR Sri (Public Health Perspective Journal, 2022)
Covid-19 is a disease caused by SARS-CoV-2 and is a new type of disease that causes a health emergency in the world. It had declared a pandemic by WHO on March 11, 2020. Covid-19 must be watched out for because of its rapid transmission, with high morbidity and mortality. Everyone got the potential to be infected by the coronavirus, with no exception a military group such as Indonesian National Army/Tentara Nasional Indonesia (TNI). In it, the spread can occur quickly without showing any symptoms, so that it has the potential to cause an outbreak. There were Covid-19 cases was found, as many as 82 soldiers were detected as infected by Covid-19. It could interfere with the main task of the TNI as the front line of military forces in dealing with threats to state sovereignty, maintaining territorial integrity, and safe the Unitary State Indonesian Republic. This research aims to analyze the determinants of the occurrence of Covid-19 in soldiers of a TNI unit who had finished carrying out combat training for one month in 2020. This research is an analytical survey research with a case-control approach. The research population was 400 TNI soldiers who had completed their combat in a forest area in Sumatera. The samples that were successfully obtained based on the inclusion and exclusion criteria are 82 respondents (41 as cases, and 41 as control), with purposive technique using a questionnaire. Data processing used univariate analysis, bivariate analysis, and multivariate analysis. There was a frequency distribution test, rank Spearman correlation test, and ordinal logistic regression test. The results showed a significant influence between health protocol behavioral factors, smoking habits, and blood type on the incidence of Covid-19 with a p-value 0.05. There was no influence between the history of influenza vaccination and the incidence of Covid-19, with a p-value 0.05. The health protocol behavioral variables are the most dominant factors influencing the incidence of Covid-19 in TNI training soldiers.